2004
DOI: 10.22358/jafs/67401/2004
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive evaluation of meat traits of ducks from two sire strains

Abstract: Compared with strain A44, male and female ducks of strain A55 showed significantly higher body weights at 7 weeks of rearing. They did not differ only in shank length and breast muscle thickness. Dressing percentage and percentage of tissue components were similar in both strains. Only the percentage of skin with subcutaneous fat and weight of abdominal fat were lower in A55, which is a favourable result. The weights of breast and leg muscles were found to be positively and significantly correlated with the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 2 publications
5
14
2
Order By: Relevance
“…The mean fat percentage in the fresh and cooked meat sample of breast muscle of both species were lower than the mean fat percentage in thigh muscle. This finding was in contrast with the result obtained by Mazanowski and Ksiazkiewicz (2004) in Pekin ducks and Isguzar et al, (2002) in local ducks and Turkish Pekins. The protein content of both fresh and cooked breast meat samples of both species were significantly higher when compared to that of the values of fresh and cooked thigh meat samples of both.…”
Section: Nscontrasting
confidence: 88%
“…The mean fat percentage in the fresh and cooked meat sample of breast muscle of both species were lower than the mean fat percentage in thigh muscle. This finding was in contrast with the result obtained by Mazanowski and Ksiazkiewicz (2004) in Pekin ducks and Isguzar et al, (2002) in local ducks and Turkish Pekins. The protein content of both fresh and cooked breast meat samples of both species were significantly higher when compared to that of the values of fresh and cooked thigh meat samples of both.…”
Section: Nscontrasting
confidence: 88%
“…Live body weights obtained in all 49-day-old groups were higher compared with 2975 g for Pekin hybrids AP57 and PP54 obtained by Bernacki et al (2006), Pekin pure strain A55-2943 g (Mazanowski and Książkiewicz, 2004) and 2887 g (Adamski et al, 2005), fed commercial feeds recommended for slaughter ducks. Also, after 56 days of rearing, the average live body weights of the experimental and control group were higher than the 3014 g reported by Bernacki et al (2006) for Pekin hybrids.…”
Section: Discussionmentioning
confidence: 51%
“…The slaughter yield of 49-day-old ducks from the control group and groups fed 15 and 25% DDGS was significantly lower (P<0.05) compared with Pekin hybrids AP57 (68.2%) and PP54 (68.9%) (Bernacki et al, 2006), but similar to the 66.0% obtained by Mazanowski and Książkiewicz (2004) for P55. Despite the lower slaughter yield, the average proportion of total muscle was not significantly affected by either age at slaughter or DDGS level, and was comparable to Pekin strain P66 (25.7%) (Witkiewicz et al, 2006) and hybrid PP54 (25.1%) (Bernacki et al, 2006).…”
Section: Discussionmentioning
confidence: 59%
“…Similar results for the effect of Pekin duck strains on breast muscle weight were obtained by Smith et al (2015), who concluded that breed had little effect on drip loss and on lightness (L*) and redness (a*) values of the breast muscles. In a study characterizing meat traits and meat quality of Pekin-type ducks strains A-44 and A-55, selected in Poland, the meat of A-55 ducks was found to have higher culinary value (Mazanowski et al, 2003;Mazanowski & Książkiewicz, 2004;Adamski et al, 2005).…”
Section: Introductionmentioning
confidence: 99%